Sistem Pengurusan Kedai Pokok Uteh Ices Garden - Fadzil, Muhammad Fikri; SALAMAT, MOHAMAD AIZI (Applied Information Technology And Computer Science, 2023)
Now, in the millennial age, technology is changing. Technological advancements affect all element of life, from social to economic. The Uteh Ices Garden tree shop management system is a web-based system designed to make tree information administration easier at the Uteh Ices Garden tree store. The store manager has had some issues with manual information management. To address the issue, the Uteh Ices Garden tree shop management system was created. The Agile technique was used to design this system. This methodology is widely used in the system development sector, making it useful to use indirectly. Planning, analysis, design, development, experimentation, deployment, and feedback are all phases of this technique. The system is also built with software, such as php and xampp, as well as hardware, such as laptops. Finally, this project is expected to meet the aims and goals of consumer demands and wants while also resolving shop management issues.